Komik Digital Interaktif Meningkatkan Hasil Belajar Materi Memakan dan Dimakan Peserta Didik Kelas V SD Negeri Rembul 01 - I'malus Sholikha; Barokah Isdaryanti (FONDATIA, 2026)
This study was motivated by low learning outcomes in the IPAS subject on the “memakan dan dimakan” (eating and being eaten) topic at SD Negeri Rembul 01 due to limited and non-varied learning resources. The study aimed to develop an interactive digital comic and assess its effectiveness in improving students’ learning outcomes on the “memakan dan dimakan” topic. A Research and Development (R&D) model with an ADDIE design was employed, involving 36 fifth-grade students, consisting of 6 students in a small-scale trial and 30 students in a large-scale trial. Data were collected through tests, questionnaires, interviews, and observations, and were analyzed using the Shapiro–Wilk normality test, paired-sample t-test, and N-gain test. The results of the media expert (97.65%) and material expert (92.85%) evaluations indicated that the interactive digital comic was in the “highly feasible” category. The t-test significance value of 0.000 in both testing scales and the high N-gain values of 0.76 in the small-scale trial and 0.77 in the large-scale trial confirmed the effectiveness of the interactive digital comic in improving students’ learning outcomes. These findings are consistent with Mayer’s Cognitive Theory of Multimedia Learning regarding the integration of visual–verbal media and support the research objective of strengthening students’ conceptual understanding of the “memakan dan dimakan” topic. The study’s implications provide a practical basis for teachers to utilize interactive technology in IPAS learning at the elementary level and offer a theoretical contribution to the development of digital media literacy studies in the context of primary education.